Efficiency, Scale Economies, and Profitability of the US Commercial and Savings Banks: Recent Evidence - Nawaz, Md. Asif (2019)
The importance of researching the ways of building an efficient and stable banking sector encouraged the endeavour of pursuing this research. With an unbalanced panel of 454 US banks including 394 commercial and 60 savings banks and 5265 observations, this study has analysed both efficiency and profitability of these banks during 2003-2018. The use of Battese and Coelli (1995) Stochastic Frontier model provided the chance of simultaneously estimating the efficiency levels of the banks and analysing the determinants of cost and profit efficiency. Further, the System Generalised Method of Moments (SGMM) is used to investigate the important bank-specific, industry-specific, and macroeconomic determinants of US commercial and savings banks’ profitability. The efficiency results indicate that the overall cost efficiency is statistically higher than the profit efficiency with a score of 92.1% and 63.59% respectively. Although the global financial crisis did not affect cost efficiency much, but it had a shattering effect on the profit efficiency of the US banks. Moreover, it is found that savings banks in the USA are more cost efficient than the commercial banks and commercial banks are more profit efficient than savings banks; there is no significant differences between the cost and profit efficiencies of privately or publicly owned banks; and foreign banks are less cost and profit efficient compare to their domestic counterparts. Furthermore, the medium, large and very large banks experienced the lowest cost and profit efficiency scores during the studied period, however, on average banks are enjoying economies of scale in terms of the outputs produced. Besides, among the three largest banks chosen for bank level efficiency analysis, Bank of America suffered most in terms of both cost and profit efficiency, J.P. Morgan Chase experienced the most vulnerable profit efficiency and Wells Fargo’s profit efficiency score is the most stable one and had always been the highest. The analyses of the determinants of cost and profit inefficiency influencing determinants reveal that the cost inefficiency gets reduced with the increase of US commercial and savings banks’ capital level, banking industry’s concentration level, and with the economic growth. However, increase in banks’ assets, liquidity, operating expenses, and non-performing loans, and increase in US economy’s unemployment, inflation, money supply, and interest rate boost the cost inefficiency among the considered banks. On the other hand, the increase of commercial and savings banks’ size, operating expenses, non-performing loans, and capital level help in reducing profit inefficiency; whereas, increased market concentration, economic growth and interest rate increase the profit inefficiency of these banks. Finally, the profitability determinants analysis uncovers that profitability is significantly positively influenced by the previous years’ profit, current bank size and inflation; whereas, banks’ capital level, market capitalisation, and money supply in the economy found to be having significantly negative impact on the profitability of the US commercial and savings banks.